Bioactive properties and compounds in fruiting bodies and mycelia of Pleurotus eryngii (DC.) Quél and Suillus bellinii (Inzenga) Watling - Souilem, Fedia (2018)
Mushrooms have been used as sources of natural compounds for pharmaceutical applications. Not just fruiting bodies, but also their mycelium have been recognized as important sources of bioactive molecules. Pleurotus eryngii (DC.) Quél, in particular, is widely consumed due to its nutritional value and bioactive properties. On the other hand, Suillus bellinii (Inzenga) Watling is known as an ectomycorrhizal symbiont whose bioactivity has been scarcely studied. In the present work, each one of this species (fruiting body, mycelium and culture media) was characterized in terms of wellrecognized bioactive compounds namely, phenolic acids and ergosterol, by high performance liquid chromatography coupled to a photodiode array or an ultraviolet detector, respectively. The antioxidant activity of the samples was evaluated by four different assays: free radical scavenging activity, reducing power, b-carotene bleaching inhibition and thiobarbituric acid reactive substances (TBARS) assay. The cytotoxic activity, was evaluated either in human tumor cell lines (MCF-7- breast adenocarcinoma, NCI-H460- non-small cell lung cancer, HeLa- cervical carcinoma and HepG2- hepatocellular carcinoma), as also in a non-tumor porcine liver cells established in-house (PLP2). S. bellinii fruiting body and its mycelium showed higher contents of ergosterol and phenolic acids, and higher antioxidant activity than P. eryngii counterparts, Nevertheless, P. eryngii mycelium showed a cytotoxicity similar (sometimes superior) to its fruiting body, in comparison with S. bellinii mycelium that presented a lower anti-proliferative activity than its fruiting body. Overall, P. eryngii and S. bellinii, as well as their mycelia and culture media can be used as sources of bioactive compounds or as ingredients to be included in applications with antioxidant and cytotoxic properties.